A Study on China-Bangladesh Relations in the Context of the Geopolitical, Security, Strategic and Economic Interests of India - Hoque, Md. Selimul; Sheema, Sharmila Kabir; Das, Monish; Ahamed, Akkas (Advances in Social Sciences Research Journal, 2025)
The geopolitical dynamics of South Asia have changed significantly in the twenty-first century, with Bangladesh emerging as a vital participant in China’s regional cooperation and development. This article investigates the emerging economic and strategic partnership between China and Bangladesh, examining its security, economic and strategic implications for India, particularly in light of Bangladesh’s recent political shift. As China has decided to strengthen commercial and defense ties with Bangladesh, India’s traditional regional influence faces an increasing threat in recent time. The study investigates how Bangladesh’s growing reliance on Chinese investments and military backing, threaten India’s security, trade and impact regional stability. By studying the China- Bangladesh geopolitical and economic relations this article aims to provide a thorough understanding of India’s security, economic, regional and strategic goals in both South and Southeast Asia. This study has found that a strong relationship between China and Bangladesh might jeopardize India’s regional interests in South and Southeast Asia. But, a strong and cordial relationship among China-Bangladesh and India, is of course, in favor of India’s Interests. The study is based on secondary data, focus group discussions and observation methods. Finally the study has provided with some policy recommendations so as to improve the relationship among China, India and Bangladesh. After all, regional developmemt, economic cooperation and cultural ties in the whole region are very essential.